Preparation and characterization of gadolinium-loaded PLGA particles surface modified with RGDS for the detection of thrombus - Zhang Y (Dove Medical Press, 2013)
Yu Zhang,1 Jun Zhou,1 Dajing Guo,1 Meng Ao,2 Yuanyi Zheng,2 Zhigang Wang21Department of Radiology, the Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 2Institute of Ultrasound Imaging, Department of Ultrasound, the Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of ChinaAbstract: Thrombotic disease is a leading cause of death and disability worldwide. The development of magnetic resonance molecular imaging provides potential promise for early disease diagnosis. In this study, we explore the preparation and characterization of gadolinium (Gd)-loaded poly (lactic-co-glycolic acid) (PLGA) particles surface modified with the Arg-Gly-Asp-Ser (RGDS) peptide for the detection of thrombus. PLGA was employed as the carrier-delivery system, and a double emulsion solvent-evaporation method (water in oil in water) was used to prepare PLGA particles encapsulating the magnetic resonance contrast agent Gd diethylenetriaminepentaacetic acid (DTPA). To synthesize the Gd-PLGA/chitosan (CS)-RGDS particles, carbodiimide-mediated amide bond formation was used to graft the RGDS peptide to CS to form a CS-RGDS film that coated the surface of the PLGA particles. Blank PLGA, Gd-PLGA, and Gd-PLGA/CS particles were fabricated using the same water in oil in water method. Our results indicated that the RGDS peptide successfully coated the surface of the Gd-PLGA/CS-RGDS particles. The particles had a regular shape, smooth surface, relatively uniform size, and did not aggregate. The high electron density of the Gd-loaded particles and a translucent film around the particles coated with the CS and CS-RGDS films could be observed by transmission electron microscopy. In vitro experiments demonstrated that the Gd-PLGA/CS-RGDS particles could target thrombi and could be imaged using a clinical magnetic resonance scanner. Compared with the Gd-DTPA solution, the longitudinal relaxation time of the Gd-loaded particles was slightly longer, and as the Gd-load concentration increased, the longitudinal relaxation time values decreased. These results suggest the potential of the Gd-PLGA/CS-RGDS particles for the sensitive and specific detection of thrombus at the molecular level.Keywords: poly (lactic-co-glycolic acid), Arg-Gly-Asp-Ser peptide, magnetic resonance imaging, thrombus, particle